One-Pot Synthesis of Polysubstituted Imidazoles Based on Pd(OAc)2/Ce(SO4)2/Bi(NO3)3 Trimetallic Cascade of Decarboxylation/Wacker-Type Oxidation/Debus–Radziszewski Reaction - Sun, Wei; Zhang, Mingjuan; Li, Peilang; Li, Yiqun (Synthesis, 2019)
A novel and highly efficient one-pot synthesis of polysubstituted imidazoles from α-hydroxyphenylacetic acids, diphenylacetylene, and amines has been achieved by Pd(OAc)2/Ce(SO4)2/Bi(NO3)3 trimetallic catalytic system. A series of control experiments showed that this overall reaction occurs through a one-pot cascade process combining the steps of decarboxylation of α-hydroxyphenylacetic acids, Wacker-type oxidation of diphenylacetylene, and Debus–Radziszewski annulation of aryl aldehydes and benzil generated in situ, as well as amines. This reaction represents a novel multicomponent reaction using α-hydroxyphenylacetic acids and diphenylacetylene as sources of aryl aldehydes and a β-diketone. This process exhibits a broad substrate scope and a good functional group tolerance to assemble the corresponding polysubstituted imidazoles in excellent yields (72–88%) under mild conditions.
Keywords: PdII/CeIV/BiIII trimetallic system; imidazole; decarboxylation; Wacker-type oxidation; Debus–Radziszewski reaction